How do Capital Market Pressures Affect Pay Structures? Evidence Based on Short Selling and Firms’ Internal Pay Gaps - Li, Xinghan (Transactions on Social Science, Education and Humanities Research, 2024)
This paper examines the relationship between short selling and internal pay gaps of listed companies, and explores how short selling affects the company’s pay structure. To this end, this paper utilizes the data of Chinese A-share listed companies from 2008 to 2022, and adopts the staggered-DID method, and finds that short selling significantly increases the internal pay gaps of firms subject to the short selling mechanism, but gaps are instead narrowed in SOEs and technology-intensive firms. The mechanism analysis suggests that short selling widens pay gaps by increasing the demand for highly educated managers and their compensation for job risk. The result of this paper provides a new perspective for understanding the socio-economic effects of capital market policies, as well as a rationale for formulating fair and reasonable pay policies.